Cassation-Level Sentencing Disparities and the Future of Criminal Justice in Indonesia - Lisa Rahmasari; Hery Firmansyah (Jurnal Ilmu Hukum Kyadiren, 2026)
Sentencing disparities in serious criminal cases frequently generate debate concerning fairness, legal certainty, and the consistency of judicial decision-making, as reflected in the commutation of the death penalty to life imprisonment in Supreme Court Decision Number 813 K/Pid/2023 involving FS. This study aims to analyze sentencing disparities between appellate and cassation court decisions and to examine the implications of sentencing reforms under Law Number 1 of 2023 concerning the Criminal Code for judicial reasoning patterns and sentencing proportionality. The study employs a normative legal research method using statutory, case, conceptual, and comparative approaches, analyzed through a qualitative framework. The findings indicate that vertical sentencing disparities arise from differing penal philosophies adopted by the judex facti and judex juris. Furthermore, the 2023 Criminal Code has begun to shape judicial reasoning toward a more rehabilitative and humanistic approach to punishment. The study concludes that penal reform requires clearer sentencing guidelines to promote consistency in judicial decisions, strengthen legal certainty, and achieve substantive justice.